Genotyping of hepatitis B virus from dried and stored serum on filter paper (Medical Journal of Indonesia, 2005)
HBV genotype has aclose association with prognosis and therapy as well as for epidemiology study. However, this examination can be done only in large cities that are not practical to send serum sample due to geographical burden and facilities. The aim of this study is to know whether HBV genotype can be determined from dried and stored serum on filter paper and compare the result with sera drawn directly from chronic hepatitis B (CHB) and hepatoma patients. Twenty-three serum samples were obtained from CHB patients. HBV DNA were quantitatively determined with Cobas Amplicor HBM (Roche Diagnostics GmBH, Germany) and dropped on to 3 x 1 cm filter papers. After allowed to dry in a plastic clip, it were put in a closed envelope then stored for 1 week in room condition (27 – 33 oC). DNA extraction were done from the filter papers after a short incubation period and HBV genotypes were determined with PCR and specific primers. For comparison, 20 CHB-Hbe(+) samples and 29 hepatoma samples were drawn directly and not dried. HBV genotype were detected in 18/23 (78.2%) from dried serum samples on filter paper while in sera that were not stored, from CHB-HBe(+) samples, 20/20 (100%) could be determined while from hepatoma patients, 24/29 (82.7%) samples. The proportion of genotype were in line with other reported HBV genotype examination for Indonesia. It is concluded that detection of HBV genotype can be done from dried serum in filter paper and stored for 1 week. (Med J Indones 2005; 14: 215-9)